Influence Of Rooting Media And Indole-3-Butyric Acid (IBA) Concentration On Rooting And Shoot Formation Of Warburgia Ugandensis Stem Cuttings - Akwatulira, Florence; Gwali, Samson; Okullo, John Bosco Lamoris; Ssegawa, Paul; Tumwebaze, Susan Balaba; Mbwambo, John Richard (African Journal of Plant Science, 2011)
This study investigated the influence of different rooting media and indolebutryic acid (IBA) hormone concentration on root and shoot development in stem cuttings ofWarburgia ugandensis. Stem cuttings were treated with three different levels (0.3, 0.6 and 0.8% w/w) of IBA concentration (including a control- no IBA hormone) and propagated in three rooting media (milled pine bark, top forest soil and sand) under non-misting propagators. Data on root and shoot development, callusing, number and length of roots and shoots were analyzed using analysis of variance (ANOVA) and Chi square test. Callusing, root and shoot development were significantly (p<0.05) influenced by rooting media and IBA concentration. Milled pine bark and 0.8% w/w IBA concentration gave the highest percentages of stem cuttings that callused, rooted and shooted (38, 37, 41% and 57, 41, 59%), respectively. Similarly, milled pine bark and 0.8% w/w IBA concentration gave the greatest number and longest roots and shoots per stem cutting. Vegetative propagation of W. ugandensis through stem cuttings can be appropriately achieved by treating the cuttings with 0.8% w/w IBA hormone using milled pine bark as a growth medium.
Keywords: Warburgia ugandensis, indolebutryic acid (IBA), vegetative propagation, callusing, rooting, milled pine bark.